Gamification-based intervention for enhancing team effectiveness and coping flexibility: Randomized controlled trial - Cheng, Cecilia; Chau, Chor-lam (Frontiers in Psychiatry, 2022)
This study aimed to evaluate a newly developed gamification-based intervention of serious play training (SPT). A randomized controlled trial was conducted to assess the efficacy of the new intervention program in comparison with a widely adopted cognitive-behavioral training (CBT) program. Real-life work teams were recruited to enhance the ecological validity of outcome evaluation. The participants comprised 250 Chinese working adults (68% men; median age=25 years, range: 18–40) who took part voluntarily. They were randomly assigned to the SPT, CBT, and waitlist conditions. For outcome evaluation, team effectiveness was the primary outcome, whereas coping flexibility was the secondary outcome. For explanation of outcome changes, group cohesion and discriminative thinking were tested as the hypothesized learning mechanisms. The results revealed that the SPT group alone reported greater team effectiveness over time, with an increase in group cohesion found to explain the improvement. Both the SPT and CBT groups reported greater coping flexibility over time, with discriminative thinking found to account for the beneficial changes. These findings provide initial evidence indicating the efficacy of utilizing the gamification approach in corporate training for team-building and personal coping.